Wielokulturowość – zagrożenie czy wyzwanie? Spojrzenie teologiczno-moralne - Janiszewska, Anna (Społeczeństwo, 2022)
The aim of article is an attempt to show the phenomenon of multiculturalism as a theological-moral problem. In this context it has also shown the importance of attitudes such as tolerance, respect and cultural identity. Also emphasized the openness of Christianity and the Catholic Church for people from all cultures and nations.